PEMBELAJARAN KOLABORATIF PADA DALAM MATA PELAJARAN ILMU PENGETAHUAN SOSIAL TERPADU - Layli, Nurul (Solidarity: Journal of Education, Society and Culture, 2012)
Collaborative learning model is one model of learning that is expected to streamline the learning process so as to make students more active and creative. This study aims at knowing the planning, the application, and the challenge of using collaborative learning in Social Scienes at MTs Roudlotusysyubban Pati. The results showed that teachers do not have the training about collaborative learning and the teachers faced many barriers in the application of collaborative learning. These barriers include the lack of teachers in English-language skills, limited learning time, the inability of students for peer learning, and the limited medium of instructions..